Reliability engineering - Rao, Singiresu S. (Boston: Pearson, 2015)
This book is intended for use as an introduction to reliability engineering, including the aspects of analysis, design, testing, production, and quality control of engineering components and systems. The material can be used for senior or dual-level courses on reliability. The mathematical background necessary in the area of probability and statistics is covered briefly to make the presentation complete and self-contained. Expanded explanations of the fundamental concepts are given throughout the book, with emphasis on the physical significance of the ideas. Numerous analytical and numerical examples and problems are used to illustrate the principles and concepts. The solution of probability and reliability problems using the commonly used software systems, such as MATLAB and excel, is also presented.
Introduction -- Basic probability theory -- Random variables and probability -- External distribution -- Functions of random variables -- Time-dependent reliability of components and systems -- Modeling of geometry, material strength, and loads -- Strength-based reliability -- Design of mechanical components and system -- Monte carlo simulation -- Reliability-based optimum design -- Failure modes, event-tree, and fault-tree analyses -- Reliability testing -- Quality control and reliability -- Maintainability and availability -- Warranties
Includes Index
Keywords: Statistics -- Reliability Theory